Decay-Accelerating Factor 1 Deficiency Exacerbates Leptospiral-Induced Murine Chronic Nephritis and Renal Fibrosis - Ferrer, Maria Florencia (2014)
Leptospirosis is a global zoonosis caused by pathogenicLeptospira, which can colonize the proximal renal tubules andpersist for long periods in the kidneys of infected hosts. Here, we characterized the infection of C57BL/6J wild-type andDaf12/2mice, which have an enhanced host response, with a virulentLeptospira interrogansstrain at 14 days post-infection,its persistence in the kidney, and its link to kidney fibrosis at 90 days post-infection. We found thatLeptospira interroganscan induce acute moderate nephritis in wild-type mice and is able to persist in some animals, inducing fibrosis in theabsence of mortality. In contrast, Daf12/2mice showed acute mortality, with a higher bacterial burden. At the chronic stage,Daf12/2mice showed greater inflammation and fibrosis than at 14 days post-infection and higher levels at all times thanthe wild-type counterpart. Compared with uninfected mice, infected wild-type mice showed higher levels of IL-4, IL-10 andIL-13, with similar levels ofa-smooth muscle actin, galectin-3, TGF-b1, IL-17, IFN-c, and lower IL-12 levels at 90 days post-infection. In contrast, fibrosis in Daf12/2mice was accompanied by high expression ofa-smooth muscle actin, galectin-3, IL-10, IL-13, and IFN-c, similar levels of TGF-b1, IL-12, and IL-17 and lower IL-4 levels. This study demonstrates the link betweenLeptospira-induced murine chronic nephritis with renal fibrosis and shows a protective role of Daf1.